Detection of Tectonic and Crustal Deformation using GNSS Data Processing: The Case of PPGnet - Epameinondas Lyros; Jakub Kostelecky; Vladimir Plicka; Filler Vratislav; Efthimios Sokos; Konstantinos Nikolakopoulos (Civil Engineering Journal, 2021)
Aitolo-Akarnania prefecture, western Greece, is an area with strong earthquakes and large active fault systems. The most prominent are the Katouna sinistral strike slip fault and the Trichonis Lake normal fault system. Their proximity to large cities, and the lack of detailed information on their seismogenic potential, calls for multiparametric research. Since 2013, the area’s crustal deformation has been monitored by a dense GNSS Network (PPGNet), consisting of five stations, equipped with Leica and Septentrio receivers. The objective of this network is to define the rate of deformation across these two main fault systems. Data is recorded using two sampling frequencies, 1 Hz and 10Hz, producing hourly and daily files. Daily data is processed using Bernese GNSS Processing Software using final orbits of International GNSS Service. Double-difference solution is computed using phase measurements from the PPGNet network complemented by four stations from Athens’ National Observatory GNSS network and six stations from METRICA network. First results show a NNE movement at PVOG station of 12 mm/y and a similar movement at RETS station of about 9 mm/y. This means that the Trichonis Lake normal fault system, located between these two stations, depicts a slip rate of 3 mm/y. KTCH and RGNI stations move eastwards at a velocity of about 5 mm/y due to the Katouna-Stamna fault system. Data from PPGNet has provided important results on crustal deformation in the area, i.e. slip rates have been attributed to specific fault systems. The comparison and links of these data with broader geodynamic models is now possible and we expect, in a later phase that will provide a more detailed image of the associated seismic hazard for Aitolo-Akarnania. Doi: 10.28991/cej-2021-03091633 Full Text: PDF